“Ja Sagen”: Katakan “Ya” pada Kehidupan (Kajian Narasi Pergulatan Eksistensial dalam Film Theory of Everything) - Oktarizal Drianus; Diah Meitikasari; Emil Niti Kusuma (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
In the midst of the phenomenon that brings the trap and temptation to say “no” to life, Theory of Everything movie comes against it. The study tracks the narrative of existential twists in the film Theory of Everything (2014) which tells the life journey of famous science writer Stephen Hawking. This study uses the existentialism approach with the Clark and Braunn thematic analysis techniques. The existential themes that are exposed include: 1) faith and destiny; 2) freedom of will, choosing to live or die; 3) the empowering love; 4) suffering as an integral part of living; 5) humor, self-acceptance and achievement. All these themes can be summarized in the statement that life, however sweet and bitter, must still be lived. “Ja Sagen”: Say “yes” to life.